Effects of internal irreversibility and heat leakage on the finite time thermoeconomic performance of refrigerators and heat pumps - Kodal, A; Sahin, B; Yilmaz, T (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
By using finite time thermodynamic theory, a performance analysis based on the thermoeconomic criterion has been performed for an irreversible refrigerator and a heat pump. The thermoeconomic objective function is defined as the cooling load for the refrigerator and the heating load for the heat pump per unit total cost. The optimal performances and design parameters which maximize the objective functions are investigated. The design parameters under the optimal conditions have been derived analytically, and then, the effects of internal irreversibility, heat leakage and the economical parameter on the global and optimal performances have been discussed. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: finite time thermodynamics; thermoeconomic optimization; irreversible refrigerator; irreversible heat pump; ABSORPTION REFRIGERATOR; OPTIMUM PERFORMANCE; DRIVEN; CYCLES; OPTIMIZATION; SYSTEM; ENGINE; Thermodynamics; Energy & Fuels; Mechanics